PENGEMBANGAN MODUL AJAR BERBASIS BUDAYA JAWA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIS SISWA PADA MATERI BANGUN DATAR DI KELAS IV UPT SPF SD NEGERI 101921 BERINGIN - Safitri, Devi; Devi Safitri, Ahmad Landong; Mawarni, Elsa; Khairunisa, Novia Futty; Nuraminah, Nuraminah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Creating an understanding of complex concepts certainly requires an appropriate model to support student stimuli in thinking scientifically, particularly in mathematics learning. Ethnomathematics-based learning is a pedagogical approach that relates to the real world by applying ethnomathematics in the classroom learning process. The implementation of this method is carried out by integrating local cultural elements into the learning materials. This research aims to investigate students' responses to Javanese culture-based teaching modules and to determine the validity, practicality, and effectiveness of Javanese culture-based teaching modules in improving students' mathematical learning outcomes. This type of research employs the Research and Development (R&D) method with the ADDIE model. The results of the study show that the average validation assessment score from media experts is 4.5%, categorized as "Highly Acceptable". The assessment score from content experts also averages 4.5%, categorized as "Highly Acceptable". Evaluation scores from teachers average 3.75 with a percentage of 93.75% categorized as "Very Interesting". The test results from the fourth-grade students at UPT SPF SDN 101921 Beringin show an average pre-test score of 25.3% and a post-test score of 81.5%, indicating an improvement in the learning outcomes of fourth-grade students at UPT SPF SDN 105359 Sumberjo.